2019
DOI: 10.1186/s12872-019-1002-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of myocardial infarction, atrial fibrillation, acute stroke, acute kidney injury and delirium after cardiac surgery – a sub-analysis of the RIPHeart-Study

Abstract: BackgroundThe aim of our study was the identification of genetic variants associated with postoperative complications after cardiac surgery.MethodsWe conducted a prospective, double-blind, multicenter, randomized trial (RIPHeart). We performed a genome-wide association study (GWAS) in 1170 patients of both genders (871 males, 299 females) from the RIPHeart-Study cohort. Patients undergoing non-emergent cardiac surgery were included. Primary endpoint comprises a binary composite complication rate covering atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Similar to other reports, a significant association has been shown between the minor allele (A) of TNF-α (-308 G/ A) and the severity of AKI (Susantitaphong et al, 2013), and organ dysfunctions in septic patients (Wang et al, 2017). In contrast, a larger study did not find any association between the above SNPs with AKI (Westphal et al, 2019). Likewise, TNF-α (-308) polymorphism was not associated with progression into AKI in patients with severe sepsis (Payen, 2019), and in patients following cardiac surgical interventions (Boehm et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Similar to other reports, a significant association has been shown between the minor allele (A) of TNF-α (-308 G/ A) and the severity of AKI (Susantitaphong et al, 2013), and organ dysfunctions in septic patients (Wang et al, 2017). In contrast, a larger study did not find any association between the above SNPs with AKI (Westphal et al, 2019). Likewise, TNF-α (-308) polymorphism was not associated with progression into AKI in patients with severe sepsis (Payen, 2019), and in patients following cardiac surgical interventions (Boehm et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Human chondrocytes will be used for verification in future experiments. Emerging evidence has demonstrated that DUSP4 serves a regulatory role in cell inflammation, injury and apoptosis in a variety of diseases (9,22,23). However, the exact mechanism underlying DUSP4 in OA is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study cohort, one genome-wide association study (GWAS) has been undertaken and did not identify an association of the MIF gene polymorphisms with postoperative outcome [ 47 ]. Therefore, our findings underscore the necessity of candidate gene studies, including of common structural variants such as microsatellite repeats that are not detectable by SNP-based GWAS platforms [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same study cohort, one genome-wide association study (GWAS) has been undertaken and did not identify an association of the MIF gene polymorphisms with postoperative outcome [ 47 ]. Therefore, our findings underscore the necessity of candidate gene studies, including of common structural variants such as microsatellite repeats that are not detectable by SNP-based GWAS platforms [ 47 , 48 , 49 ]. As technological advances and declining costs in next-generation sequencing technologies pave the way for the broader availability of genomic testing, the implementation of genetic susceptibility data will help to improve risk stratification and to reduce the incidence and sequelae of cardiac surgery [ 50 ].…”
Section: Discussionmentioning
confidence: 99%